Enlightenment philosophy and scepticism - Sztajer, Sławomir (Humaniora. Czasopismo Internetowe, 2020)
The article discusses the role of scepticism in the Enlightenment. For many historians of philosophy, Enlightenment was a hiatus in the history of scepticism. Ideas often attributed to the Enlightenment, such as the cult of reason, optimism and the belief in progress, seem to be contrary to scepticism. I argue that this simplistic view of the Enlightenment is far from reality. The Enlightenment not only brought forth such great followers of scepticism as Hume, but also influenced other thinkers in many different ways. The influence of scepticism is not always clearly visible in the philosophical works of that time. Moreover, few philosophers would describe themselves as sceptics. Nevertheless, if one considers different ways in which scepticism influenced Enlightenment philosophy, it becomes apparent that the assertion that scepticism was allegedly absent in the Enlightenment is untenable.